Identifikasi Kandungan Timbal dan Krom Pada Air Tanah di Sekitar Tempat Pewarnaan Kampung Industri Tenun Kota Kediri - Marianingsih Marianingsih; Afifah Nur Aini (Pena Medika Jurnal Kesehatan, 2020)
Industrial development, the textile besides provide benefits to the people can also cause pollution problems. The high use of dyes on industrial activity, for example chromium and lead impact in improving the amount of pollution and waste that it. This research aimed at identifying lead and chrome on groundwater around the staining in Kampung Industri Tenun Kota Kediri. Methods used is descriptive , with the total sample as many as 8 ground water. The result showed the chrome on the entire sample of ground water